Current evidence on the use of sugammadex for neuromuscular blockade antagonism during electroconvulsive therapy: a narrative review - Vivek Arora; Laurence Henson; Sandeep Kataria (Korean Journal of Anesthesiology)
Depression is a common mental health problem that is associated with significant disability and mortality. Electroconvulsive therapy (ECT) has been demonstrated to be effective at resolving expression of suicidal intent in patients with depression. In less acute situations, patients are usually referred for ECT after several medication trials. Neuromuscular blocking agents (NMBAs) are used to block tonic-clonic motor activity and associated physical harm during the delivery of ECT. Succinylcholine (Sch), with its rapid onset of muscle relaxation, short self-terminating duration of action, and rapid subsequent return of spontaneous ventilation, is the NMBA of choice for ECT. However, the use of Sch is problematic or contraindicated is some situations. Although non-depolarizing NMBAs can be used, the variable time to onset of adequate muscle relaxation and prolonged duration of action have limited their widespread acceptance as alternatives to Sch. Recently, however, with the widespread availability of sugammadex, a chemically modified γ-cyclodextrin that rapidly and predictably reverses the effect of non-depolarizing NMBAs, the muscle relaxation achieved by rocuronium can predictably and effectively be reversed. In situations where Sch is contraindicated or otherwise problematic, rocuronium, followed by pharmacological antagonism with sugammadex, can provide a safe and effective muscle relaxation approach comparable to that of Sch in terms of duration of action. This review provides a summary of the current state of evidence for the use of sugammadex during ECT, which should lend support to further acceptance and future studies of sugammadex in the context of ECT.